2019
DOI: 10.35940/ijrte.d7127.118419
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the Semantic Web Reasoners

Deepika Chaudhary*,
Jaiteg. Singh,
D.P. Kothari

Abstract: The major benefit of working on Ontology Web Language (OWL) is its ability to define semantics such that the information becomes more valuable. To realize the full power of semantics, it is essential to integrate a reasoning engine to it. The software codes that perform inferences are often referred to as reasoning engines or reasoners. The reasoners can be classified into categories: tableau based and rule based reasoners. The rule based reasoners combines the assertions with a set of logical rules to infer n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…P. Chaudhary & A.K. Singh [11] analyzed TCP & UDP packets for communication purposes over the internet using Wireshark. They concluded that Wireshark identifies every packet in detail.…”
Section: Related Workmentioning
confidence: 99%
“…P. Chaudhary & A.K. Singh [11] analyzed TCP & UDP packets for communication purposes over the internet using Wireshark. They concluded that Wireshark identifies every packet in detail.…”
Section: Related Workmentioning
confidence: 99%